A longitudinal study of Aboriginal images in annual reports: evidence from an arts council. (15th March 2019) - Rentschler, Ruth; Subramaniam, Nava; Martin, Brian
Abstract: This paper provides a longitudinal analysis of Aboriginal and Torres Strait Islander imagery use in the annual reports (ARs) of the Australia Council for the Arts (ACA). Content analysis based on imagery, textual narrative and para‐text analyses of ARs over 43 years (1973–2015) reveals that the nature and extent of Aboriginal images in ACA's ARs systematically varies with the broader contemporary socio‐political and economic developments. Our findings provide insights on an institutional response to the portrayal and shaping of the identity of a key stakeholder group, i.e. Aboriginal artists, which are associated with gaining and maintaining organisational legitimacy.